2020
DOI: 10.1186/s40658-020-00310-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of block-sequential regularized expectation maximization reconstruction of 68Ga-DOTATOC, 18F-fluoride, and 11C-acetate whole-body examinations acquired on a digital time-of-flight PET/CT scanner

Abstract: Background: Block-sequential regularized expectation maximization (BSREM) is a fully convergent iterative image reconstruction algorithm. We hypothesize that tracers with different distribution patterns will result in different optimal settings for the BSREM algorithm. The aim of this study was to evaluate the image quality with variations in the applied β-value and acquisition time for three positron emission tomography (PET) tracers. NEMA image quality phantom measurements and clinical whole-body digital tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 29 publications
1
22
0
1
Order By: Relevance
“…Therefore, a direct comparison between present results and those of [ 13 ] is challenging. Recently Lindström et al [ 15 ] showed that for 68 Ga-DOTATOC PET/CT studies β values equal to or higher than 400 result in noise levels equal to or lower than those of OSEM (2 min/bp) with improved SNR and SBR. The OSEM reconstruction algorithm used in [ 15 ] corresponds to the algorithm recommended by the manufacturer, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a direct comparison between present results and those of [ 13 ] is challenging. Recently Lindström et al [ 15 ] showed that for 68 Ga-DOTATOC PET/CT studies β values equal to or higher than 400 result in noise levels equal to or lower than those of OSEM (2 min/bp) with improved SNR and SBR. The OSEM reconstruction algorithm used in [ 15 ] corresponds to the algorithm recommended by the manufacturer, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…For 68 Ga-DOTA, one preliminary study by Lantos et al [ 13 ] in 10 patients suggested using a β factor between 350 and 450 in clinical practice for all the studied radiopharmaceuticals while the study conducted by ter Voert et al [ 14 ] concluded that, for 68 Ga-PSMA, a β value between 400 and 550 could be optimal. A recent study conducted by Lindström et al [ 15 ] on thirteen 68 Ga-DOTATOC studies concluded that β values equal to or higher than 400 result in noise levels equal to or lower than those of OSEM (3 iterations, 16 subsets, 5-mm post-filter) with improved SNR and SBR.…”
Section: Introductionmentioning
confidence: 99%
“…• Image noise [75][76][77][78] • Subjective image quality [73,77,[79][80][81][82][83][84] • Prediction of subjective image quality from objectified measures [85] • Lesion SUV [75,86,87] • Conspicuity of pulmonary lesions [69,77,86] • Detection rate in pulmonary lesions [88] • Lesion detectability in pelvic PSMA PET/MRI at low activity [89] • Detection rate of lymph nodes in fluorocholine PET [90] • Normal databases for brain PET in neurodegenerative disease [91,92] • Acquisition time reduction [81,84,89,93] Level 2:…”
Section: Level Of Evidencementioning
confidence: 99%
“…Studies addressing whole body [ 18 F]FDG on various PET/CT scanners have shown for BSREM to reduce image noise without impeding the tumor detectability, or vice versa, to improve tumor detectability at similar noise levels as ordered-subsets expectation maximization (OSEM) ( Teoh et al, 2016 , Sah et al, 2017 , Lindström et al, 2018 , Trägårdh et al, 2019 , Bjöersdorff et al, 2019 ). Other studies have also shown the need to adjust the setting of β depending on the tracer and application being used ( Lindström et al, 2019 , Lindström et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%